INTERACTIONAL MODIFICATIONS FOR COMPREHENSIBLE INPUT: A CASE STUDY OF TWO EFL TEACHERS - Naila Karima; Didi Suherdi; Fazri Nur Yusuf (Journal of English and Education, 2017)
This study aims to investigate the use of interactional modifications proposed by Long (1982) by two English teachers and language learning opportunities obtained. The study found out the distribution and the form of interactional modification in two different levels of English proficiency, elementary and pre-intermediate. To answer the research questions, case study was adopted. The main data were six transcribed classroom interactions of six sessions with audio-video recording. From the analysis, it was found that elementary teacher modified more interactions compared to pre-intermediate teacher due to less capability of lower student to comprehend the information delivered. The form of interactional modification used was other-repetition strategy, where both of the teachers repeated student`s utterances frequently in order to clarify, confirm, or emphasize the initial utterances. Besides, the occurrences of interactional modifications were considered to be determined by several factors, such as student`s level of proficiency, material delivered, and teacher`s knowledge. As for the question of language learning opportunities, the findings revealed by modifying the interactions there were gap noticing where the teacher noticed the mistakes of student`s language used by bringing that gap into awareness. Besides, modified interactions also gave the student the chance for meaning negotiation where the understanding of information was obtained through resolving the communication breakdown in the classroom. Therefore, it is paramount for teachers to acknowledge, believe, and aware that modified interaction is important not only to provide comprehensible input but also to make student comprehend the information and are triggered to be able to participate in the conversations.